ANALISIS FISIOLOGI BAKTERI LIGNOSELULOLITIK DAN AKTINOMISETES SELULOLITIK DAN LIGNINOLITIK DARI TANAH GAMBUT DESA RIMBO PANJANG KABUPATEN KAMPAR SEBAGAI AGEN BIOKOMPOS - Novia Lestari; Rodesia Mustika Roza; Atria Martina (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
During a composting process, microorganisms such as bacteria, fungi, and actinomycetes have a role in degradation of organic matter. Temperature and pH also influence composting process. This research was aimed to obtain bacterial isolates and actinomycetes with the best ability to be applied as biocompost agent by analyzing the ability of those isolates to grow in different temperature and pH. Isolates of actinomycetes and bacteria were isolated from peatsoils in Rimbo Panjang, Kampar Regency, Riau. Bacterial isolates were inoculated into Nutrient Broth medium and actinomycetes isolates were inoculated into Starch Casein Broth medium. The cultures were incubated at room temperature (±27°C), 40°C, 50°C, 60°C, 70°C and 80°C in pH of 5 and pH of 7. The results showed that 3 isolates of bacteria and 90 actinomycetes isolates were able to grow at room temperature (±27°C) and 40°C in pH of 5 and pH of 7. A total of 28 actinomycetes isolates grew at 50°C in pH 5 and pH 7 with 2 isolates were considered as the most potential, which were Rhodococcus sp. and Streptomyces sp..